SELF-REPORTED MUSCULOSKELETAL ACUTE AND OVERUSE INJURIES AMONG LATVIAN INFANTRY SOLDIERS - Nesterovica, Darja; Vaivads, Normunds; Stepens, Ainars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Musculoskeletal injury is the leading cause of disability among different military populations that results in socioeconomic burden and negatively affects military readiness. Study aim was to describe self-reported musculoskeletal injuries among Latvian infantry soldiers during one-year period. Survey-based cross-sectional study was carried out. Data was assessed using survey about injuries that occurred in one-year period during annual medical check-up. Musculoskeletal injuries were classified according to body regions as it is in Barell injury matrix and by injury type – acute or overuse. Study results showed in one-year injury incidence rate was 867.8 cases per 1000 person-years (95% CI 824.8 – 913.0) with total 197 musculoskeletal injuries reported among active duty infantry soldiers. Typical acute injuries were superficial contusion injuries (n=24), fractures (n=21), joint dislocations (n=21) and sprains (n=29). Typical overuse diagnoses were lower back pain (n=42), patellofemoral pain syndrome (n=11), medial tibial stress syndrome (n=9), plantar fasciitis (n=8). Present study showed high incidence of overuse back injuries and overuse and acute lower leg injuries. Mostly of reported injuries could be classified as preventable and should be reduced through injury reduction programmes.